2006
DOI: 10.1128/aem.72.1.606-611.2006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Transmission of Honeybee Viruses

Abstract: Transmission mechanisms of six honeybee viruses, including acute bee paralysis virus (ABPV), black queen cell virus (BQCV), chronic bee paralysis virus (CBPV), deformed wing virus (DWV), Kashmir bee virus (KBV), and sacbrood bee virus (SBV), in honey bee colonies were investigated by reverse transcription-PCR (RT-PCR) methods. The virus status of individual queens was evaluated by examining the presence of viruses in the queens' feces and tissues, including hemolymph, gut, ovaries, spermatheca, head, and evisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
219
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(250 citation statements)
references
References 13 publications
14
219
3
1
Order By: Relevance
“…This is in agreement with other studies, which either showed high viral titres in the abdomens of infected bees (Chen et al, 2006;Iqbal & Mueller, 2007;Yue & Genersch, 2005) or directly identified the digestive tract as one of the predominantly infected tissues (Fievet et al, 2006). Further experiments are needed to analyse the spread of the virus from the midgut to other tissues.There are studies showing qualitatively that DWV is present in the midgut content (Fievet et al, 2006) and in faeces (Chen et al, 2006), suggesting a faecal-oral route of transmission, but there is no quantitative data allowing the estimation of the absolute viral titre. The same is true for absolute DWV titres in different developmental stages of the bee.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…This is in agreement with other studies, which either showed high viral titres in the abdomens of infected bees (Chen et al, 2006;Iqbal & Mueller, 2007;Yue & Genersch, 2005) or directly identified the digestive tract as one of the predominantly infected tissues (Fievet et al, 2006). Further experiments are needed to analyse the spread of the virus from the midgut to other tissues.There are studies showing qualitatively that DWV is present in the midgut content (Fievet et al, 2006) and in faeces (Chen et al, 2006), suggesting a faecal-oral route of transmission, but there is no quantitative data allowing the estimation of the absolute viral titre. The same is true for absolute DWV titres in different developmental stages of the bee.…”
supporting
confidence: 73%
“…There are studies showing qualitatively that DWV is present in the midgut content (Fievet et al, 2006) and in faeces (Chen et al, 2006), suggesting a faecal-oral route of transmission, but there is no quantitative data allowing the estimation of the absolute viral titre. The same is true for absolute DWV titres in different developmental stages of the bee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health of honeybees has been one of the most important topics in apicultural research in recent years (Genersch, 2010). This is primarily due to the recent emergence of high honeybee colony losses in many parts of the world (Le Conte et al, 2010;Neumann and Carreck, 2010;Stokstad, 2007;vanEngelsdorp et al, 2008) and the vulnerability of honeybees to parasitic mites, fungi, viruses and bacteria (Bailey and Ball, 1991;Chen et al, 2006;Dietemann et al, 2012;Genersch, 2010;Genersch et al, 2010;Martin, 2001;Ribière et al, 2010;Sammataro et al, 2000). These pathogens and parasites can have harmful effects on honeybee health and the services they offer, which in turn can lead to severe economic losses (Genersch, 2010;Morse and Calderone, 2000;Shen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that the insect eye pigment could cause false-negative PCR results and the elimination of the PCR inhibitors was achieved by cutting out eyes prior to DNA isolation (Bextine et al 2004). Our earlier study showed that deformed wing virus (DWV), one of the most prevalent and common honey bee viruses, was not detected in the head of infected bees (Chen et al 2006). However, a later publication by Genersch (2005) showed the detection of DWV in the head of infected bees when an additional step of column purification was included in the regular method of RNA extraction.…”
Section: Introductionmentioning
confidence: 99%